Proceedings of the 2014 ACM SIGSAC Conference on Computer and Communications Security 2014
DOI: 10.1145/2660267.2660272
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and Protection of Channel State Information in Multiuser MIMO Networks

Abstract: Multiple-In-Multiple-Out (MIMO) offers great potential for increasing network capacity by exploiting spatial diversity with multiple antennas. Multiuser MIMO (MU-MIMO) further enables Access Points (APs) with multiple antennas to transmit multiple data streams concurrently to several clients. In MU-MIMO, clients need to estimate Channel State Information (CSI) and report it to APs in order to eliminate interference between them. We explore the vulnerability in clients' plaintext feedback of estimated CSI to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…Wang et al [20] propose a novel Sybil attack detection based on CSI, and the detection algorithm can tell whether the static devices are Sybil attackers. Tung et al [18] evaluate sniffing attack (enables concurrently transmitting malicious clients to eavesdrop other ongoing transmissions) and power attack (enables malicious clients to enhance their own capacity at the expense of others') and they propose a novel CSI feedback system to prevent CSI forging without requiring any modification at the client side.…”
Section: Related Workmentioning
confidence: 99%
“…Wang et al [20] propose a novel Sybil attack detection based on CSI, and the detection algorithm can tell whether the static devices are Sybil attackers. Tung et al [18] evaluate sniffing attack (enables concurrently transmitting malicious clients to eavesdrop other ongoing transmissions) and power attack (enables malicious clients to enhance their own capacity at the expense of others') and they propose a novel CSI feedback system to prevent CSI forging without requiring any modification at the client side.…”
Section: Related Workmentioning
confidence: 99%
“…In [10], the authors mainly analyzed the influence on Quality-of-Service (QoS) for honest receivers caused by various forms of malicious channel feedback, and showed that the presence of just a single adversary could degrade the system performance significantly. Then, for the purposes of eavesdropping and selfish, the impact of channel state misreporting of a malicious user was studied in [4] for a multi-user MIMO system that broadcasts independent messages to multiple users. The proposed "sniffing attack" is an example of the channel direction modified CSI misreporting, which enables the attacker to eavesdrop the signal sent to the legitimate user.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed "sniffing attack" is an example of the channel direction modified CSI misreporting, which enables the attacker to eavesdrop the signal sent to the legitimate user. Besides, the "power attack" proposed in [4] is to manipulate the Access Point's power allocation. By modifying the reported channel magnitude, the adversary can enhance its own capacity at the expense of others'.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, in [7,8], Schulz et al presented an attack toward [6] under an multi-antenna eavesdropper setting. In [13], Tung et al showed two active, single-antenna attacks toward MIMO systems protected by orthogonal blinding.…”
Section: Introductionmentioning
confidence: 99%